PERTUMBUHAN, HASIL PANEN & KANDUNGAN VITAMIN C TANAMAN KALE (Brassica oleracea var. Acephala) ORGANIK PADA BEBERAPA PERLAKUAN CAMPURAN KOMPOS CAIR BERBAHAN UTAMA URIN KELINCI, SUSU SAPI SEGAR, DAN TELUR AYAM KAMPUNG - Jose Natanael; Dina Rotua Valentina Banjarnahor (Jurnal Penelitian Pertanian Terapan, 2021)
Minang Bangkit Merbabu farmers apply organic agriculture in form of administrating liquid compost with main materials that consist of rabbit urine, fresh cow milk, and chicken eggs as nutrient provider. This research’s main purpose is to know the effect of liquid compost toward growth, yield, and vitamin C content of organic kale. This research took place in Salaran Experimental Field, Faculty of Agriculture and Business, Satya Wacana Christian University, between March to May 2020. There are one control and four treatment mixtures of several liquid compost materials with codes CBK1, CBK2, CBK3, CBK4 which will be repeated six times and multiplied by two to test the yield and vitamin C content to obtain 60 experimental units. This research used a randomized block design, with vitamin C levels as a quality parameter, yield parameters in the form of wet and dry root and canopy weight, and growth parameters in the form of number of leaves, stem diameter, and crown diameter. Data were analyzed using variance test with Tukey follow-up test with α=5%. Based on the results of the variance test, the mixture of several compost materials had a significantly different effect on all parameters. The CBK4 treatment showed the best growth and yields including 15.17 leaf number, 0.97 cm stem diameter, 52.42 cm crown diameter, 10.01 g root crop and 101.37 g crown. The vitamin C content in kale showed significantly different results to the control, but not significantly different in treatment (CBK1, CBK2, CBK3, and CBK4)